2004
DOI: 10.1038/sj.leu.2403383
|View full text |Cite
|
Sign up to set email alerts
|

Apoptotic mechanisms in the control of erythropoiesis

Abstract: Erythropoiesis is a complex multistep process encompassing the differentiation of hemopoietic stem cells to mature erythrocytes. The steps involved in this complex differentiation process are numerous and involve first the differentiation to early erythoid progenitors (burst-forming units-erythroid, BFU-E), then to late erythroid progenitors (colony-forming unitserythroid) and finally to morphologically recognizable erythroid precursors. A key event of late stages of erythropoiesis is nuclear condensation, fol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
166
2
15

Year Published

2006
2006
2011
2011

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 207 publications
(186 citation statements)
references
References 202 publications
3
166
2
15
Order By: Relevance
“…At early stages of acquired myelodysplastic syndromes, exacerbation of the physiological pathway to caspase activation in erythroid cells, even in the presence of elevated Epo concentrations, is responsible for a high rate of apoptosis, ineffective erythropoiesis and increased phagocytosis (Raza et al, 1995;Bouscary et al, 1997;Hellstrom-Lindberg et al, 2001;Shetty et al, 2002;Tehranchi et al, 2003;Testa, 2004). Several observations argue for a role of the Fas-L/Fas pathway in this pathogenic event.…”
Section: Mitochondria Caspases and Hematopoietic Cell Differentiationmentioning
confidence: 99%
See 1 more Smart Citation
“…At early stages of acquired myelodysplastic syndromes, exacerbation of the physiological pathway to caspase activation in erythroid cells, even in the presence of elevated Epo concentrations, is responsible for a high rate of apoptosis, ineffective erythropoiesis and increased phagocytosis (Raza et al, 1995;Bouscary et al, 1997;Hellstrom-Lindberg et al, 2001;Shetty et al, 2002;Tehranchi et al, 2003;Testa, 2004). Several observations argue for a role of the Fas-L/Fas pathway in this pathogenic event.…”
Section: Mitochondria Caspases and Hematopoietic Cell Differentiationmentioning
confidence: 99%
“…Apoptosis of megaloblastic erythroblasts upon folate or cobalamine deficiency, apoptosis of erythroblasts from patients with b-thalassemia, parvovirus B19 infection or congenital aplastic anemia and anemia from patients with multiple myeloma or rheumatoid arthritis could also be related to amplification of a physiological, mitochondria-mediated, caspase activation associated with erythroid differentiation (Testa, 2004). On the other hand, the thrombopenia observed in myelodysplastic patients was recently shown to be related to a necrosis-like, caspase-3-independent death of megakaryocytes (Houwerzijl et al, 2005).…”
Section: Mitochondria Caspases and Hematopoietic Cell Differentiationmentioning
confidence: 99%
“…The anemia is caused by excess, unbalanced alpha globin chains that are toxic to the red blood cell, leading to apoptosis of developing erythroblasts at the polychromatophilic normoblast stage with intramedullary hemolysis (Rund and Rachmilewitz 2005;Perrine 2005;Schrier 1997;Koury, Sawyer, and Brandt 2002;Centis et al 2000;Testa 2004;Mathias et al 2000;Yuan et al 1993;Pootrakul et al 2000;Silva et al 1996). The disease is characterized into two major subtypes based upon severity: betathalassemia major and beta-thalassemia intermedia.…”
Section: Introductionmentioning
confidence: 99%
“…23,28,29 Therefore, TRAIL may serve as a negative regulator of expanding clones in the distal stages of differentiation of all hematopoietic lineages. 13,[17][18][19]30,31 As umbilical cord blood (UCB) becomes an important source of hematopoietic progenitors for transplantation, we evaluated the effect of TRAIL in proximal stages of their activity. We recently showed that the Fas/Fas-ligand interaction transduces trophic signals in early stages of hematopoietic cell engraftment, 32 because the most primitive progenitors are insensitive to Fas-mediated apoptosis.…”
Section: Introductionmentioning
confidence: 99%